Effect of a phytogenic feed additive on the growth performance and immunity of Pacific white leg shrimp, Litopenaeus vannamei, fed a low fishmeal diet. Issue 2 (16th October 2020) - Kesselring, Jutta; Gruber, Christina; Standen, Benedict; Wein, Silvia
Abstract: Plant‐derived products have been suggested to partially replace fishmeal in aquafeed; however, often at decreased growth performance, inflammatory responses, and increased susceptibility to diseases. This study assessed the effects of the commercial phytogenic feed additive Digestarom PEP MGE on the growth, nutritional performance, and immune response of L. vannamei . Juvenile shrimp ( N = 540) were stocked in 36 tanks ( V = 100 L) for 63 days and fed one of the four experimental diets: (i) standard formulation (control, 24% fishmeal), (ii) low fishmeal diet (5%), (iii) low fishmeal diet plus 0.2 g/kg Digestarom PEP MGE, and (iv) low fishmeal diet plus 0.4 g/kg Digestarom PEP MGE. The results obtained after 63 days of feed supplementation suggest that the blend of essential oils tested compensated for the negative performance and health consequences of the low fishmeal diet. Particularly, the survival, FCR, total hemocyte count, and respiratory burst of the shrimp fed a low fishmeal diet supplemented with this phytogenic improved up to the levels recorded for shrimp fed a high fishmeal diet. Overall, results suggest that Digestarom PEP MGE can be incorporated into shrimp low fishmeal diets to compensate for the negative performance and immunological effects of partially replacing fishmeal with plant‐based protein.